MOTIVATION TYPES IN PREDICTING THE USE OF SECOND LANGUAGE LEARNING STRATEGIES BY ENGLISH MAJOR STUDENTS AT THE UNIVERSITY OF LANGUAGES AND INTERNATIONAL STUDIES – VIETNAM NATIONAL UNIVERSITY, HANOI - Sao, Bui Thien; Mai, Duong Thu (VNU Journal of Foreign Studies; Vol 34 No 5DO - 10.25073/2525-2445/vnufs.4306, 2018)
This study examined the role of motivation types in predicting the use of language learning strategies by English major students at the University of Languages and International Studies - Vietnam National University, Hanoi (ULIS). A questionnaire was employed to collect information from 123 students. The first section of the questionnaire was about how often the students used strategies in learning English, and the second one collected information about the participants’ levels of four motivation types. The results indicated that all the strategies were used by the majority of the respondents, and among four types of motivation, their instrumental motivation was of the highest level. Importantly, the study disclosed a significant and positive correlation between motivation and language learning strategy use. Finally, going beyond the correlational analysis already observed in many other studies, this study utilized regression analysis which then helped unveil significant contributions of integrative and intrinsic motivation to strategy use. Helpful implication can be drawn from this study.